Design and analysis of an efficient photovoltaic energy-powered electric vehicle charging station using perturb and observe MPPT algorithm - Awad, Mohamed; Ibrahim, Ahmed M.; Alaas, Zuhair Muhammed; El-Shahat, Adel; Omar, Ahmed I. (Frontiers in Energy Research, 2022)
According to the current directive, we must rely on green energy for sustainable mobility. One of the green transition’s goals is to use renewable energy to charge electric vehicles (EVs). Solar energy is a form of renewable energy sources, and it is classified as being clean, available, and renewable because it is based on sunshine. Nowadays, the world is turning to EVs which have lower running costs and cleaner environments. Lithium-ion batteries are commonly utilized to store energy in EVs. This article covers the design and analysis of a photovoltaic (PV) system to charge five models of EVs such as BMW i3 2019, Volkswagen e-Golf, Fiat 500e, Mercedes EQA 250, and Hyundai Kona Electric in a DC fast charging mode by using a buck converter to minimize the output voltage and without any addition of energy storage. By applying Perturb & Observe (P&O) Maximum Power Point Tracking (MPPT), the maximum power and efficiency from PVs are obtained. The charging time is calculated for each EV of the five models in the State of Charge (SOC) area at 20–80 percent. A MATLAB program is employed to simulate the EV models by calculating the efficiency of the MPPT controller, time of charging, and characteristic of voltage and current levels for each model of these EVs. All models are tested under the condition of irradiance level from 600 W/m2 to 1000 W/m2 and temperature between 20°C and 30°C. The results showed that the PV system is effective and economical as a stand-alone to charge EVs in a rapid charge mode.